Factors that influence the use of voluntary counseling and testing (VCT) clinics by people living with HIV/AIDS in MSM group - Ernawati, Ernawati; K, Hairuddin; Palallo, Umar Dg (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: The VCT Clinic service program is one of the early detection efforts to find out whether someone has been infected with HIV or not through Voluntary Counseling and Testing (VCT). Risky sexual behavior with HIV/AIDS is the MSM group. This study aimed to determine the factors that influence the utilization of VCT services in the MSM group. Research Methodology: This study is a type of quantitative research with an approach using a cross-sectional study design. The population in this study were all HIV/AIDS sufferers who were undergoing ARV treatment at the Kendari City Hospital in 2023, totaling 349 people. Data were analyzed using SPSS to determine the frequency distribution and the chi-square statistical test to determine the variables' relationship. Result: The results showed a relationship between knowledge and the utilization of VCT clinics by the MSM group with a closeness level of 0.517, which indicated a moderate closeness of the relationship. There was a relationship between actions and the utilization of VCT clinics by the MSM group with a closeness level of 0.343, which indicated a weak closeness of the relationship. There is a relationship between family support and the use of VCT clinics by the MSM group, with a closeness level of 0.262, indicating a weak closeness of the relationship. There is a relationship between social support and the use of VCT clinics by the MSM group, with a closeness level of 0.300, indicating a weak closeness of the relationship. Conclusion: The analysis results show a significance value of <0.05, meaning there is a relationship between knowledge, attitudes, actions, social support, and family support with the use of VCT clinic services. Suggestions: It is hoped that the Kendari City Health Office will make policies in carrying out HIV/AIDS prevention activities, especially for the MSM group, by maximizing socialization about HIV/AIDS in hotspots where the group carries out activities. In addition, it is coordinating with the Education Office to provide education and socialization to students and the community to limit and avoid factors that cause risky sexual behavior.